Makna pada Teks Desain Kemasan Jamu Khusus Wanita - Natadjaja, Listia; Tripoli, Faruk; Wahyono, Sugeng Bayu (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study examined the meanings of the texts on the packaging of jamu for women and revealed its proposed ideology. As a health product, information on the design of the packaging of jamu is not only as a means to inform consumers of the product, but also as a "tool" for manufacturers to construct meaning and convey their message and ideology. By using Roland Barthes' semiotic analysis, the researchers analyzed the texts and uncovered the denotative and connotative meanings. The findings showed that the texts on the packaging of jamu for women implies ambivalent meanings between ‘jamu’ and ‘medicine’, ‘traditional’ and ‘modern’, ‘local’ and ‘global’, ‘empirical’ and ‘science’, ‘natural’ and ‘cultural’, ‘feminine’ and ‘masculine’. The existence of an ideology of femininity and the frequent use of medical discourses that influences the construction of the texts were evident.